Intestinal microbiota changes in early life of very preterm infants with bronchopulmonary dysplasia: a nested case–control study - Ning, Tao; Shan, Xiaoxue; Zhuang, Xiaowen; Li, Bingjie; Zhang, Yuhan; Chen, Tianyu; Peng, Song; Lu, Han; Xue, Qiong; Yan, Huaiyu; Ren, Yimei; Cui, Shudong; et al. (Frontiers in Microbiology, 2025)
Background and aimBronchopulmonary dysplasia (BPD) is one of the most important complications of very preterm infants. This study was to investigate changes in the intestinal microbiota of very preterm infants with BPD.MethodsWe enrolled 50 very preterm infants at the gestational age of 24+0–31+6 weeks, categorizing them into the BPD group and control group, and fecal samples were collected on days 1, 7, 14, 21, and 28, respectively. Finally, 30 preterm infants were left after excluding 20 preterm infants. We tested and analyzed 16S rDNA of bacteria and short-chain fatty acids (SCFAs) within the feces.ResultsThe BPD group possessed a higher abundance of Ureaplasma urealyticum (UU) and a lower abundance of Bacteroidota than the control on day 1. The differences in intestinal microbiota were reduced on days 7 and 14, and no difference in SCFAs existed on day 14. New differences emerged over time, with a significant decrease of Veillonella dispar in the BPD group than in the control group on day 28, which showed a continuous decline in the BPD group over time.ConclusionIntestinal microbiota dysbiosis existed in very preterm infants with BPD. The increased abundance of UU on day 1 and the decrease of Veillonella dispar on day 28 might increase the risk of BPD.